PURCHASE DECISION LIFESTYLE - Anissa; Sabrina (SAJMR : Southeast Asian Journal of Management and Research, 2023)
The purpose of this research is to determine the extent of the influence of location, price, and lifestyle on the purchase decision at Kereey Coffee Shop, Jakarta. This study is a survey research with a quantitative approach. The research used a sample of 100 respondents and primary data sources processed with SPSS 25. The results of the study showed that the price variable (X1) partially has a significant influence on the purchase decision (Y). The location variable (X2) partially has a significant influence on the purchase decision (Y). The lifestyle variable (X3) partially has a significant influence on the purchase decision (Y). The location variable (X1), price (X2), and lifestyle (X3) simultaneously have a significant influence on the purchase decision variable (Y). Looking at the correlation coefficient value (R) of 0.875, which means there is a very strong correlation/relationship between location, price, and lifestyle towards the purchase decision. The value of the adjusted coefficient of determination (adjusted R2) is 0.758 or 75.8%, which means that the independent variables can explain 75.8% of the changes in the purchase decision variable, while the remaining 24.2% is explained by other factors outside of this study